Neurosyphilis as a great imitator: a case report. (December 2016) - Sabre, Liis; Braschinsky, Mark; Taba, Pille
Abstract Background Neurosyphilis is defined as any involvement of the central nervous system by the bacteriumTreponema pallidum . Movement disorders as manifestations of syphilis have been reported quite rarely. Case presentation We report a case of a 42-year-old Russian man living in Estonia with rapidly progressive dementia and movement disorders manifesting as myoclonus, cerebellar ataxia and parkinsonism. The mini mental state examination score was 12/30. After excluding different neurodegenerative causes, further diagnostic testing was consistent with neurosyphilis. Treatment with penicillin was started and 6 months later his mini mental state examination score was 25/30 and he had no myoclonus, parkinsonism or cerebellar dysfunction. Conclusion Since syphilis is easily diagnosed and treatable, it should be considered and tested in patients with cognitive impairment and movement disorders.